Management of the historical and cultural value of territories through the formation of historical areas of cities - Martyn А.; Novakovska, I.; Novakovsky, D. (Land Management, Cadastre and Land Monitoring, 2024)
Lands on which cultural heritage monuments, their complexes (ensembles), historical and cultural protected territories, protected archaeological territories, open-air museums, memorial museums-manors are located, in accordance with the legislation of Ukraine, belong to lands of historical and cultural purpose. The organization and establishment of the boundaries of the territories of historical and cultural purpose, restrictions on their use and their regime-forming objects is carried out in accordance with the projects and technical documentation of land management. For the territories of the nature reserve fund and other nature conservation purposes, health, recreational, historical and cultural, forestry purposes, water fund lands and water protection zones, the land legislation establishes the same procedure for developing the composition and geodetic and cartographic substantiation of land management projects, as well as for their approval and approval . This provision has existed for a long time, despite the fact that the given list combines six categories of land with different legal regimes. The boundaries of historical areas and the modes of their use are indicated in the documentation on land management, urban planning and scientific project documentation on the protection of cultural heritage, which determines the need for their mutual consistency. The article examines the legal and organizational provisions of the formation of the historical and cultural potential of the historical areas of cities. In connection with the discrepancies in the legal acts, proposals for the codification of legal norms regarding the composition and distribution of land by category, setting restrictions, regulation of construction, landscape protection zones and archaeological layer are substantiated. The proposed approaches to the definition and calculation of the economic efficiency of historical areas include a variety of methods that allow for the assessment of both quantitative and qualitative aspects of the preservation of cultural heritage.